(untitled) (African Journal of Law and Politics, 2025)
The protection of consumers’ rights is a huge challenge in the electricity sector in Cameroon. One of the main reasons for this is that the law ignores the existence of non-customer electricity consumers which, ironically, constitute the greater majority of those who use electricity. This article raises the problem of recognition and protection of the rights of this category of electricity consumers whose situation in some instances is obscure. It brings to lime light the situation of non-customer electricity consumers and determines the extent to which their rights are protected in Cameroon. Through doctrinal and empirical research, the article reveals that the legislator has not recognised noncustomer consumers of electricity in Cameroon. Fortunately, case law has recognised their rights with implication that they can enjoy the same rights with other consumers who are actually customers of the Electricity Corporation. It recommends amongst others, the adoption of a separate legislation that deals only with electricity consumers’ rights, including users who are not subscribers or customers.